2023
DOI: 10.1186/s12905-023-02451-8
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and genotype screening of human papillomavirus among women attending a private hospital in Northern Cyprus: an 11-year retrospective study

Abstract: Background Human papillomavirus (HPV) is the most common sexually transmitted pathogen both in men and women. Accumulating epidemiological evidence supports a strong association between HPV infection and cancer of the cervix, vulva, vagina, anus, and penis. Currently, data on the HPV prevalence and genotyping is lacking in Northern Cyprus, a region in which HPV vaccination is not freely accessible via the national immunization program. The aim of this study was to evaluate the HPV type-specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
(20 reference statements)
1
0
0
Order By: Relevance
“…However, infections caused by it are not among the most common in Serbian women (Figure 2), which supports the fact that HPV genotype distributions depend on local diversity. In this regard, a recent 11-year retrospective study from Cypres reported a similar prevalence (6.6%) of HR HPV 18 [32]. A linear correlation with the degree of severity of cervical abnormalities was expressed for HPV 16, but not for HPV 18, as shown in this study (Table 4) and other previously published data [3].…”
Section: Discussionsupporting
confidence: 88%
“…However, infections caused by it are not among the most common in Serbian women (Figure 2), which supports the fact that HPV genotype distributions depend on local diversity. In this regard, a recent 11-year retrospective study from Cypres reported a similar prevalence (6.6%) of HR HPV 18 [32]. A linear correlation with the degree of severity of cervical abnormalities was expressed for HPV 16, but not for HPV 18, as shown in this study (Table 4) and other previously published data [3].…”
Section: Discussionsupporting
confidence: 88%